The rhetoric aspects in Al-Qur'an as interpreted by Al-Zamakhshariyy in Al-Kashshaf / Mohamed Sulthan Mohamed Saleem - Saleem, Mohamed Sulthan Mohamed (2012)
This research addresses the rhetorical aspects in the Holy Qur'an as interpreted by al-Zamkhshariyy in his Tafsīr al-Kashshāf, and at the same time it is comprised of the different kinds of Elucidation (ʿIlm al-Bayān), aspects of semantics (ʿIlm al-Maʿānī), and arts of figures of speech (ʿIlm al-Badīʿ),which has been addressed by al-Zamkhshriyy in Sūrah al-Baqarah. This research also discusses the issue of Iʿtizal as he himself belongs to this School of thought. This research focuses on the Sūrah al-Baqarah from tafsīr al-KashshÉf as an example in rhetoric modes. This is a descriptive study based on collection of information and communique with their interpretations and defines the relationship between the facts. The research also analyzes the data in order to reach the place where he can give his own opinion for studied manifestations in the study of eloquences. The research has discovered different beautiful aspects of the study of Elucidation (ʿIlm al-Bayān), Semantics (ʿIlm al-Maʿānī), mentioned in sūrah al-Baqarah in tafsīr al-Kashshaf, and this research may pave the way for the further research. The research also discusses ÑIlm al-BayÉn, and its kinds like al-TashbÊh, al-IstiÑarah , alkināyah and studies Ilm al-MaʿānÊ and its kinds as well, like al-Khabar , al-Inshāʾ, al-TaqdÊm, al-TaʾkhÊr , al-TawkÊd, al-Qaṣr, al-×adhaf, al-Dhkir al-IÊjāz, al-Iṭnāb, al-Waṣal wa al-Faṣal, al-Iltifāt and some aspects of ʿIlm al-BadÊʿ. The reason research had not discussed the ʿIlm al-BadÊʿ in detail is that al-Zamakhshriyy has discussed only ʿIlm al- MaʿānÊ and ÑIlm al-Bayān in his Tafsīr. And secondly ʿIlm al-BadÊʿ is not an independent science but is a demonstration for ʿIlm al-Bayān and ÑIlm al-MaʿānÊ. At the end of the research we have found many aspects of Elucidation which has been discussed in Surah al-Baqarah in tafsīr al-Kashshāf and therefore it can be concluded that there are different arts in this tafsīr which require linguistic, grammatical and Semantics study with their different kinds.